1990
DOI: 10.1002/art.1780331012
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex genes and susceptibility to systemic lupus erythematosus

Abstract: Susceptibility to systemic lupus erythematosus is associated with major histocompatibility complex (MHC)-encoded genes. We have used nucleotide sequence analysis to better define the disease-associated MHC alleles. HLA-DR2, DQwl, and especially the rare allele DQPl.AZH confer high relative risk (RR = 14) for lupus nephritis in a Caucasian population of patients. Pilot studies using historical controls suggest that these genes also confer a high risk in non-Caucasian ethnic groups (RR = 24-78). We have found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(38 citation statements)
references
References 62 publications
4
30
1
2
Order By: Relevance
“…These antigens are tightly linked constituting a class II haplotype that has been associated with 2 recognized AD, namely systemic lupus erythematosus and multiple sclerosis. 48,49 The importance of this genetic background may partly explain the recurrent disease in one of our patients, who was DR3/DR15-, DR51/DR52-, and DQ2/DQ6-positive. Finally, the term of de novo AIH may also be controversial as it is possible that the immune response is initiated against nonnative proteins of the grafted liver.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These antigens are tightly linked constituting a class II haplotype that has been associated with 2 recognized AD, namely systemic lupus erythematosus and multiple sclerosis. 48,49 The importance of this genetic background may partly explain the recurrent disease in one of our patients, who was DR3/DR15-, DR51/DR52-, and DQ2/DQ6-positive. Finally, the term of de novo AIH may also be controversial as it is possible that the immune response is initiated against nonnative proteins of the grafted liver.…”
Section: Discussionmentioning
confidence: 77%
“…We studied HLA class I and II polymorphism by standard complement-dependent microcytotoxicity assays and/or by PCR with sequence-specific primers for the following antigens/alleles: A (1,2,3,11,23,24,25,26,29,30,31,32,33,34,66,68,69,80), B (7,8,13,18,27,35,37,38,39,41,42,44,45,47,48,49,50,51,52,53,55,56,57,58,60,61,62,63,64,65,67,70,73), Cw (1,2,3,4,…”
Section: Methodsmentioning
confidence: 99%
“…Recent analyses by a British group have also shown that the development of rheumatoid arthritis in MCTD patients is associated with DR4 or DRI excluding DRBl"C1103 (11). An association between DQBlh0502 and lupus nephritis was reported in Caucasian patients with SLE (12). In North American patients with SLE, methionine at position 14 and leucine at position 26 in the DQBl pl domain, which are common among DQBl'"O602, DQBI'''0201, and DQB1":0302, were speculated to be important for anti-&DNA antibody production (3).…”
Section: Discussionmentioning
confidence: 97%
“…The study population consisted of 80 children with SLE who had onset of disease at age <18, who were being followed up by the rheumatology services at Texas Children's Hospital (Houston) and The Hospital for Sick Children (Toronto), or by the Division of Clinical Immunology and Rheumatology or the Division of Pediatric Nephrology at the University of Alabama at Birmingham. There were 38 Caucasian children (7 boys, 31 girls), 29 black children (4 boys, 25 girls), and 13 Asian children (1 boy, 12 girls). The 80 children with childhood-onset SLE were divided into 2 groups according to age at disease onset.…”
Section: Methodsmentioning
confidence: 99%